As variações do insólito em José J. Veiga - Turchi, Maria Zaira (Organon, 2005)
This article focuses on the main themes and aesthetic aspects ofJosé J. Veiga’s stories, analyzing the magical realism and the fantastic issueswithin the boundaries of his fiction.